Differences in nitrogen cycling and soil mineralisation between a eucalypt plantation and a mixed eucalypt and Acacia mangium plantation on a sandy tropical soil. Issue 1 (2nd January 2017) - Tchichelle, Sogni Viviane; Epron, Daniel; Mialoundama, Fidèle; Koutika, Lydie Stella; Harmand, Jean-Michel; Bouillet, Jean-Pierre; Mareschal, Louis
Abstract : Sustainable wood production requires appropriate management of commercial forest plantations. Establishment of industrial eucalypt plantations on poor sandy soils leads to a high loss of nutrients including nitrogen (N) after wood harvesting. An ecological intensification of eucalypt plantations was tested with the replacement of half of the Eucalyptus urophylla × E. grandis by Acacia mangium in the eucalypt monoculture to sustain soil fertility through enhancement of the N biological cycle. A randomised block design was set up on ferralitic arenosol in the Congolese coastal plains to assess differences in soil N mineralisation, N fluxes in litterfall, and N stocks in forest floor litter and soil between pure acacia (100A), pure eucalypt (100E) and mixed-species treatments (50A50E). Soil N mineralisation was enhanced under acacia, reaching on average 0.17 and 0.15 mg kg −1 soil d −1 in 100A and 50A50E, respectively, compared with 0.09 mg kg −1 soil d −1 in 100E. Higher amounts of N returning to the soil through harvest residues and litterfall were observed under acacia than under eucalypt. However, N stock in mineral soil was not increased in 100A and exhibited a limited increase only in the top soil layer of 50A50E. Our results suggest a much faster N turnover under acacia than under eucalypt. Although A. mangium is an exotic N2 -fixing tree in central Africa, it appears to be well adapted to the climatic and edaphic conditions of the Congo, showing an efficient growth strategy. Eucalypt trees could benefit from the increase in soil N availability in mixed-species stands.